Interaction models between humans and lower-limbs exoskeletons applied to robotic neurorehabilitation - Mosconi, Denis; Siqueira, Adriano A. G. (Anais Estendidos do Simpósio Brasileiro de Robótica e Simpósio Latino-Americano de Robótica (SBR/LARS); 2021: Anais Estendidos do XIII Simpósio Brasileiro de Robótica e XVIII Simpósio Latino Americano de Robótica, 2021)
Development of interaction controls applied to robots of robotic-assisted therapy is a challenge, as it requires physical contact between human and robots, in addition to demanding a high cost of time and resources. The purpose of this work was to develop a human-exoskeleton interaction model and a simulation algorithm for development, validation and testing of interaction controls applied in robotic rehabilitation of lower-limbs. Two simulations with different interaction models and controls were run, combining experimental and computational data. The results obtained proved that both the interaction model and the simulation algorithm are feasible, useful, improving flexibility and agility for developing of interaction controls.